Optimization of formulated artificial diets with the addition of sterols and cryoprotectants for effective rearing and fitness of Eldana saccharina Walker (Lepidoptera: Pyralidae) - Ngomane, Nomalizo Carol (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.